Fe2Mo3O8/exfoliated graphene oxide : solid-state synthesis, characterization and anodic application in Li-ion batteries - Maseed, Hussen (2020)
An Fe2Mo3O8/exfoliated graphene oxide (EG) composite with unique morphology is synthesized by a novel solid-state reduction method. Graphene oxide (GO), FeC2O4·2H2O and MoO3 are heated together at 750 °C for 8 h under an Ar atmosphere to obtain Fe2Mo3O8/EG as the resultant material. The morphology of the as-synthesized Fe2Mo3O8/EG powder as observed in electron micrographs confirmed the presence of layer-like EG and densely populated Fe2Mo3O8 hexagonal platelets. Thermogravimetric analysis showed that Fe2Mo3O8 and EG are in the composite at 98 and 2 wt%, respectively. The structural analysis of the as-synthesized Fe2Mo3O8/EG confirmed that Fe2Mo3O8 platelets are crystallized in the hcp crystal system. Raman scattering analysis further confirmed the presence of Fe2Mo3O8 and EG in the as-synthesized Fe2Mo3O8/EG composite. X-ray photoelectron spectroscopy confirmed that Fe and Mo elements are in the II and IV oxidation states in the as-synthesized Fe2Mo3O8/EG composite, which when tested as an anode material of a half-cell Li-ion battery, exhibited a high reversible capacity of 945 mA h g−1 at 50 mA g−1 current rate. This work paves the way to synthesize other graphene–metal oxide composites (with unique metal oxide morphologies) for their use as anode materials in Li-ion batteries.